Evils of Contemporary Society: A Study of the Plays of Vijay Tendulkar and Girish Karnad: The Burden of Social Norms on Women in Contemporary Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Society plays a very important role in the life of a person. A person has to lead his/her life according to the norms of the society. Society has fixed the role of man and woman. If he/she revolts the established norms, he/she has to suffer at the hand of the society. But to some extent a woman has to suffer more because of these norms. Society expects a woman to follow all the norms. If she is unable to follow, her life will become miserable. She is unable to get respect in the society.